The effect of drying temperature towards quantity and quality of palm oil extracted from dried decanter cake - Nur Syamiera Nabila , Masri (2012)
The production of palm oil by the palm oil refinery produces a large quantity of waste. One of the wastes produced is palm oil decanter cake. Decanter cake is generated by the separation process of the suspended solids from crude palm oil in a decanter. Usually, the generated decanter cake still contains about 8% of oil in it. So, this research described the extraction of the residual oil from the decanter cake and its quality resulting from the pretreatment applied on the decanter cake before the extraction. There are three stages involved which are the pretreatment of the decanter cake, the extraction of oil from the pretreated decanter cake, and the analysis of the extracted oil. The pretreatment method is the drying of the decanter cake to remove the moisture content of the decanter cake for optimal extraction performance. The decanter cake samples were dried at different temperature in the range of 60°C to 120°C. All dried decanter cake samples were then analyzed using Thermal Gravimetric Analysis to determine the water, volatile compound and the fixed carbon content of each dried decanter cake. Base on the weight loss profile, the samples showed only slight differences in water, volatile compound and fixed carbon content. The extraction of the oil from the decanter cake was done with Soxhiet extraction method using hexane as solvent. The decanter cake dried at 100°C sample gives the highest oil yield. The quality of the extracted oil was analyzed using acid and iodine value analysis. The oil extracted from dried decanter cake of 60°C has the highest acid value. The acid value decreases with increase in drying temperature and reach a constant value for oil from decanter cake dried at 100°C. The iodine value of extracted oil initially decreases with drying temperature and reach a minimum for sample dried at 100°C and increases at higher drying temperature. These result suggested the optimum temperature for drying under the condition of this study is 100°C. The range of the iodine value obtained was 40-50. The iodine value for the crude palm oil and cooking oil are 13.8 and 55.0.